Depression, stress, and weight loss in individuals with metabolic syndrome in SHINE, a DPP translation study. (24th September 2014) - Trief, Paula M.; Cibula, Donald; Delahanty, Linda M.; Weinstock, Ruth S.
<x xml:space="preserve">Abstract</x> Objective To examine the relationships between elevated depression symptoms (EDS) or stress and weight loss in SHINE, a telephonic, primary‐care based, translation of the Diabetes Prevention Program. Methods N = 257 adults with metabolic syndrome were randomized to individual (IC) or group (CC) phone participation. Weight, depression, anti‐depressant use (ADMs), and stress (baseline, 6 months, 1 and 2 years) were assessed. Univariate analyses used linear and logistic regression, t tests for continuous variables and exact tests for categorical variables. Stratified analyses assessed modifiers of effects of depression/stress on weight loss. Results Approximately 35% reported EDS, with no change over time. Approximately 28% of all participants used ADMs. Participants with EDS had lower mean % weight loss and a smaller % who achieved ≥5% weight loss. Participants with EDS were less likely to be "completers" (40.1% vs. 61.5%, P = 0.002), coached (48.0% vs. 60.7%, P = 0.049), or log diet/activity (19.4% vs. 42.7%, P < 0.001), behaviors related to weight loss. Results were similar for high stress. ADM use had no independent effect on weight loss. Conclusions Individuals with metabolic syndrome and EDS and/or high stress were less likely to lose significant weight. Pre‐intervention depression and stress screening to intervene may improve weight loss.